BIOLOGY AND MEASURES TO COMBAT TRIANULE GELMENTS IN CHILDREN - Sharipova F. S.; Nosirova B. M. (Web of Journals Publishing, 2024)
The relevance of the topic is that parasitic diseases are common among children today, as well as infectious diseases. Diseases caused by parasitic chickens are called helminthosis. Such diseases adversely affect the growth of boolas. Purpose and function of the Cylinders are especially common among the population. Among them, Pakana nightmare (Hymenolepis nana) is the causative agent of human hymenolepidosis. It is common everywhere and is more common in children.